An analysis of mitotic catastrophe induced cell responses in melanoma cells exposed to flubendazole - Rudolf, K; Rudolf, E (Toxicology in vitro, 2020)
Mitotic catastrophe induced by mictotubule-targeting drugs such as benzimidazole carbamates has been demonstrated to be an efficient mechanism for suppression of tumor cells growth and proliferation, with variable resulting endpoints. The present study was designed to explore some of these endpoints; i.e. the apoptosis as well as autophagy and their related signaling in several stabilized cell lines as well as human explant melanoma cells treated with flubendazole (FLU). FLU-induced mitotic catastrophe resulted in mitochondrial and caspase-dependent apoptosis, which occurred at various rates in all treated cells during 96 h of treatment. The process was characterized by enhanced transcriptional activity of TP53 and NF-κB as well as upregulated Noxa expression. Also, inactivation of Bcl-2, BclXL and Mcl-1 proteins by JNK mediated phosphorylation was observed. Although increased autophagic activity took place in treated cells too, no discernible functional linkage with ongoing cell death process was evidenced. Together these results advance our evidence over the effectiveness of FLU cytotoxicity-related killing of melanoma cells while calling for more extensive testing of melanoma samples as a prerequisite of further preclinical evaluation of FLU antineoplastic potential.
Keywords: nádorový supresorový protein p53; senioři; autofagie; Cell Cycle; Mebendazole; nádorové buněčné linie; JNK Mitogen-Activated Protein Kinases; apoptóza; lidé; Melanoma; mebendazol; Middle Aged; mitóza; Autophagy; mužské pohlaví; cytochromy c; Tumor Suppressor Protein p53; Cell Line, Tumor; protein MCL-1; membránový potenciál mitochondrií; Antineoplastic Agents; buněčný cyklus; Mitosis; melanom; protinádorové látky; Humans; Proto-Oncogene Proteins c-bcl-2; lidé středního věku; Myeloid Cell Leukemia Sequence 1 Protein; Cytochromes c; JNK mitogenem aktivované proteinkinasy; Membrane Potential, Mitochondrial; Aged; protoonkogenní proteiny c-bcl-2; Male; Apoptosis